The Determinants of U.S. Treasury Bill Rates: An Approach Based on A Vector Autoregressive Model (VAR) - Fadiga, Ismael Tanou (2009)
This dissertation examines the determinants of U.S. Treasury bill rates based on vector autoregressions for the period 1959-2009. Our main conclusions are: (1) monetary base, inflation rate and output affect the dynamics of Treasury bill rates and those results are consistent with the theory in regards to the factors affecting yield curves. Accurately, we find that the growth rates of monetary base, inflation and output are all significant in explaining the growth of U.S. Treasury bill rates; (2) criticisms mentioned in the literature against Sims' (1980) unrestricted VAR are right concerning such statistical results as impulse responses and variance decompositions, since we show that our results are sensitive to different specifications of our models. Thus, the robustness of our unrestricted VARs, even stable, might be questioned; (3) unrestricted VARs can be usefool tools for forecasting U.S. Treasury bill rates, in particular if VAR orders are based on relevant selection criteria.